Estimation of Accuracy of Umbilical Venous Catheter Insertion Depth using Body Weight or Body Measurement at a Tertiary Care Hospital in Peshawar - Murtaza, Shumaila; Razzaq, Asma; Shah, Syed Awais ul Hassan; Rahman, Asbah; Ibrahim, Sadaf; Ahmad, Shakeel (Pakistan Armed Forces Medical Journal, 2026)
Objective: To determine the accuracy of Umbilical Venous Catheter (UVC) depth of insertion using the body weight or body measurement method. Study Design: Quasi-experimental study. Place and Duration of Study: Neonatal Intensive Care Unit of Combined Military Hospital, Peshawar Pakistan, from Jan to Jun 2023. Methodology: A total of 60 neonates who were passed UVC were included in the study. UVC depth insertion estimation was done by either Shukla method or by Dunn Normogram. Group-A had UVC depth of insertion estimated by body weight, while the Group-B had estimation using body measurement. Various demographic and clinical factors were recorded. The accuracy of UVC placement was then determined on an antero-posterior chest radiograph. Results: Mean gestational age of 60 babies was 35.10±1.88 weeks and mean weight was 2.10±0.43kg. Of these 24(56.7%) were male babies, 41(68.3%) were born prematurely, 35(58.3%) had UVC placed on first or second day of life. Overall, success of a well-aligned UVC was 66.7% i.e. 40 neonates. UVC was well aligned in 16(53.3%) of the neonates measured by Shukla method, and 24(80%) plotted by Dunn Normogram. There was a statistically significant difference between methods (p=0.02). Conclusion: The study concluded that a majority of Umbilical Venous Catheter (UVCs) are well aligned irrespective of the method used. When compared, the assessment by body measurement method fares significantly better than body weight method.